Hydrological evolution of the eastern tropical Pacific during the last 430,000 years - Hasrizal Shaari (apan: Hokkaido University, 2014)
The eastern tropical Pacific (ETP) is a key region in paleocenography to understand the response of upwelling, the position of the intertropical convergence zone (ITCZ), and the zonal and meridional atmospheric circulations to orbital forcing.